Kaiser Konstantin als Leser Panegyrik, performance und Poetologie in den carmina Optatians - Körfer, Anna-Lena (Millennium-Studien / Millennium Studies, 2019)
To honor the 20th year of his reign, Emperor Constantine was given what may be the most precious gift of his lifetime: a codex of artistic panegyrics and odes dedicated to him by the poet Optatianus. Optatianus' poems showcase the poetic talent of their creator and go beyond the classical confines of a panegyric: they form a literary invitation to an intellectual bond between laudator and laudandus.